The Influence of Different Structures of Single-Knit Fabric on the Comfort Properties of Clothes - Samuel Martin Pradana; Tommy Yacob Hariandja; Sukma Yudistira; Siti Isma Sari Lubis (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
The purpose of this research is to determine the characteristics of variations in knitted structures on the comfort properties of materials in the form of porosity and moisture management properties in single knits fabrics. This research was carried out by varying the mesh structure in the form of all knit, knit knit – knit tuck, and variations of knit tuck – tuck knit, which then looked for the porosity value of the material using the image processing method of tresholding color map images by looking at the size of the empty space between materials. To see the properties of moisture management in single knit fabrics can be seen by looking at the value of air permeability, and the moisture management tester. From the experimental results, it was found that the porosity test results for structure 1 obtained a porosity value of 22.04%, for structure 2 it was 29.2% and for structure 3 it was 30.2%. where the test results show that the mesh structure with knit-knit tuck is the best mesh structure with an air permeability value of 735 cm3/cm2/s, and an OMMC value of 0.7447.